THE ORIGINS OF THE FORMATION OF THE PRINCIPLES OF THE LAW OF ROMANO-GERMANIC LEGAL FAMILY - Задорожний, Ю. А. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
This publication studies the problems of the origins of the formation of the principles of law. The article argues that the principles of Roman law, filled with organic rationality and justice, were borrowed from European countries and served as a basis for the development of new fundamental principles that became a key element of the legal system of the Romano-Germanic legal family.